Vision and Perception : A Conversation with Kalanit Grill-Spector. - Burton, Howard (Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Kalanit Grill-Spector, Professor in Psychology and the Stanford Neurosciences Institute at Stanford University. Kalanit Grill-Spector is a vision specialist with a background in computational neuroscience. Her research examines how the brain processes visual information and perceives it. This wide-ranging conversation explores how functional imaging techniques are used to visualize the brain in action and how it functions to recognize people, objects and places. Kalanit also discusses how the anatomical and functio.
Description based upon print version of record.
Keywords: Grill-Spector, Kalanit -- Interviews.; Visual perception.; Visual Perception; Perception visuelle.; visual perception.; Vision.; HEALTH & FITNESS.; Neurology.; MEDICAL.; Ophthalmology.; Neuroscience.; Life Sciences.; SCIENCE.; Visual perception; Interviews